simple adding exponents problem

Sep 2009
242
6
I'm a little tangled up with these exponents involving the imaginary unit. Can someone please confirm that I did this right?


\(\displaystyle iws^{iw-1}s^{2iw}=iws^{3iw-2iw}=iws^{iw}\)



Thanks
 

Prove It

MHF Helper
Aug 2008
12,897
5,001
I'm a little tangled up with these exponents involving the imaginary unit. Can someone please confirm that I did this right?


\(\displaystyle iws^{iw-1}s^{2iw}=iws^{3iw-2iw}=iws^{iw}\)



Thanks
\(\displaystyle iws^{iw - 1}s^{2iw} = iws^{iw - 1 + 2iw}\)

\(\displaystyle = iws^{3iw - 1}\).
 
  • Like
Reactions: rainer